2022
DOI: 10.1097/qai.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large B-Cell Lymphoma in the Public-Sector of Johannesburg, South Africa, in the Era of Widescale Antiretroviral Therapy Use

Abstract: Individual and in-training subscription rates include print and access to the online version. Institutional rates are for print only; online subscriptions are available via Ovid. Institutions can choose to purchase a print and online subscription together for a discounted rate. Institutions that wish to pur chase a print subscription, please contact Wolters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
0
1
Order By: Relevance
“…Survival rates in this study were very much poorer than is typically reported in high income countries, a finding which we have documented previously [30]. Important contributors to this finding were late case presentation and/or aggressive disease, as over 40% of the patients who died did so within one month of diagnosis, with 20% dying before any chemotherapy could be administered.…”
Section: Discussioncontrasting
confidence: 46%
“…Survival rates in this study were very much poorer than is typically reported in high income countries, a finding which we have documented previously [30]. Important contributors to this finding were late case presentation and/or aggressive disease, as over 40% of the patients who died did so within one month of diagnosis, with 20% dying before any chemotherapy could be administered.…”
Section: Discussioncontrasting
confidence: 46%
“…As we have reported previously ( Vaughan et al., 2022 ; Vaughan et al., 2023 ), survival rates in this cohort were poor as compared to those reported in high income countries (5 year survival rates over 60%) ( Sehn and Salles, 2021 ), as well as in two regional studies, one performed in Malawi among 86 adult patients with a HIV-seropositivity rate of 59% (2 year survival rate of 38%) ( Painschab et al., 2019 ), and the other in a South African study among 36 patients with HIV-DLBCL (2 year overall survival ~40%) ( de Witt et al., 2013 ). This was at least partially attributable to a very high early death rate (~30%), with over half of the patients who demised early doing so before they could be given chemotherapy.…”
Section: Discussionsupporting
confidence: 78%